2013
DOI: 10.4049/jimmunol.1202889
|View full text |Cite
|
Sign up to set email alerts
|

Human Skin Mast Cells Express Complement Factors C3 and C5

Abstract: We examine whether complement factor C3 or C5 is synthesized by human skin–derived mast cells and whether their synthesis is regulated by cytokines. C3 and C5 mRNAs were assessed by RT-PCR, and proteins by flow cytometry, confocal microscopy, Western blotting, and ELISA. C3 and C5 mRNAs were each expressed, and baseline protein levels/106 cultured mast cells were 0.9 and 0.8 ng, respectively, and located in the cytoplasm outside of secretory granules. C3 accumulated in mast cell culture medium over time and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 97 publications
0
21
0
Order By: Relevance
“…The classical and alternative pathways are the main pathways induced by radiotherapy on the transcriptional level ( Figures 1D and S1C). Because NF-kB, JAK, and STAT transcriptional pathways (Chen et al, 2011;Fukuoka et al, 2013;Hasegawa et al, 2014;Huang et al, 2002), as well as S100 calcium-binding proteins A8 and A9 (S100A8, S100A9) (Schonthaler et al, 2013) are involved in the transcription of complement factors, we analyzed such pathways by immuno-blot and found an increased production of STAT 1, STAT 2, STAT 3, NF-kB, and JAK and increased phosphorylation of STAT 2, STAT3, and JAK ( Figure S1D) 4 hr, but not (A-E) Mice were injected with B16F10-OVA cells and received radiotherapy 12 days later. (A) Tumor growth curves, (n = 5 mice per group).…”
Section: Radiotherapy Induces Complement Activationmentioning
confidence: 99%
“…The classical and alternative pathways are the main pathways induced by radiotherapy on the transcriptional level ( Figures 1D and S1C). Because NF-kB, JAK, and STAT transcriptional pathways (Chen et al, 2011;Fukuoka et al, 2013;Hasegawa et al, 2014;Huang et al, 2002), as well as S100 calcium-binding proteins A8 and A9 (S100A8, S100A9) (Schonthaler et al, 2013) are involved in the transcription of complement factors, we analyzed such pathways by immuno-blot and found an increased production of STAT 1, STAT 2, STAT 3, NF-kB, and JAK and increased phosphorylation of STAT 2, STAT3, and JAK ( Figure S1D) 4 hr, but not (A-E) Mice were injected with B16F10-OVA cells and received radiotherapy 12 days later. (A) Tumor growth curves, (n = 5 mice per group).…”
Section: Radiotherapy Induces Complement Activationmentioning
confidence: 99%
“…Complement is known to be expressed in a variety of skin cells, such as mast cells [93], macrophages [94], keratinocytes [95] and fibroblasts [96]. This suggests skin has its own complement synthesis system, like retina and vessel wall (see above).…”
Section: Inflammaging In Skinmentioning
confidence: 99%
“…From mast cells different subsets exist, which are often classified based upon the presence of the serine proteases tryptase and chymase. It was demonstrated that different subsets of MC express C5 and C3 [46,47]. Human skin mast cells showed a diffuse cytoplasmic labelling of both C3…”
Section: Mast Cellsmentioning
confidence: 99%